A new apparatus for modelling excavations. Issue 1 (March 2012) - Lam, Sze Yue; Elshafie, Mohammed Z. E. B.; Haigh, Stuart K.; Bolton, Malcolm D.
Abstract : Underground space is commonly exploited both to maximise the utility of costly land in urban development and to reduce the vertical load acting on the ground. Deep excavations are carried out to construct various types of underground infrastructure such as deep basements, subways and service tunnels. Although the soil response to excavation is known in principle, designers lack practical calculation methods for predicting both short- and long-term ground movements. As the understanding of how soil behaves around an excavation in both the short and long term is insufficient and usually empirical, the judgements used in design are also empirical and serious accidents are common. To gain a better understanding of the mechanisms involved in soil excavation, a new apparatus for the centrifuge model testing of deep excavations in soft clay has been developed. This apparatus simulates the field construction sequence of a multi-propped retaining wall during centrifuge flight. A comparison is given between the new technique and the previously used method of draining heavy fluid to simulate excavation in a centrifuge model. The new system has the benefit of giving the correct initial ground conditions before excavation and the proper earth pressure distribution on the retaining structures during excavation, whereas heavy fluid only gives an earth pressure coefficient of unity and is unable to capture any changes in the earth pressure coefficient of soil inside the zone of excavation, for example owing to wall movements. Settlements of the ground surface, changes in pore water pressure, variations in earth pressure, prop forces and bending moments in the retaining wall are all monitored during excavation. Furthermore, digital images taken of a cross-section during the test are analysed using particle image velocimetry to illustrate ground deformation and soil–structure interaction mechanisms. The significance of these observations is discussed.